Misconceptions of Quitters Students in Solving Algebra Problems Using a Two-Tier Multiple Choice Diagnostic - Kusuma, Adinda Dwi Raysha Adis; Wahyuni, Indah (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
Understanding students' misconceptions about algebra material is essential to determine corrective steps, so students avoid making continuous errors in learning algebra. This study used a qualitative approach to identify students' misconceptions about solving algebraic problems, especially quitters. The subjects in this study were class VII students of SMP Argopuro Panti who were included in the quitters' type. The instruments used were an adversity quotient questionnaire, a two-tier multiple-choice diagnostic test instrument, and an interview guide. The results of this study are in the form of misconceptions by quitters students, namely: 1) in working on subtraction questions in algebraic forms, students only subtract the first term; 2) students experience misconceptions in operating numbers; 3) students experience misconceptions about patterns for algebraic exponents; and 4) students make conceptual errors in using the cross out system. To overcome this, teachers can provide accurate explanations, use appropriate learning models, and recall student prerequisite material before learning new material. By identifying students' misconceptions in solving algebraic problems, the teacher can correct and improve students' inaccurate understanding.Memahami miskonsepsi siswa pada materi aljabar penting dilakukan agar dapat menentukan langkah perbaikan sehingga siswa tidak melakukan kesalahan yang berkelanjutan dalam pembelajaran aljabar. Penelitian ini menggunakan pendekatan kualitatif yang bertujuan untuk mengidentifikasi miskonsepsi siswa, khususnya siswa quitters, dalam menyelesaikan soal aljabar. Subjek dalam penelitian ini yaitu siswa kelas VII SMP Argopuro Panti yang termasuk dalam tipe quitters. Instrumen yang digunakan adalah angket adversity quotient, instrumen tes two-tier multiple choice diagnostic, dan pedoman wawancara. Hasil dari penelitian ini berupa miskonsepsi yang dilakukan siswa quitters, yaitu: 1) dalam mengerjakan soal pengurangan bentuk aljabar, siswa hanya mengurangi suku pertamanya saja; 2) siswa mengalami miskonsepsi dalam mengoperasikan bilangan; 3) siswa mengalami miskonsepsi mengenai pola untuk perpangkatan aljabar; dan 4) siswa melakukan kesalahan konsep dalam menggunakan sistem coret. Untuk mengatasinya guru dapat memberikan penjelasan yang akurat, penggunaan model pembelajaran yang tepat, serta mengingat kembali materi prasyarat siswa sebelum mempelajari materi baru. Dengan mengidentifikasi miskonsepsi siswa dalam mengerjakan soal aljabar, guru dapat melakukan upaya untuk mengoreksi dan memperbaiki pemahaman siswa yang kurang tepat.